A Putative Lipoprotein Mediates Cell-Cell Contact for Type VI Secretion System-Dependent Killing of Specific Competitors - Lauren Speare; Madison Woo; Anne K. Dunn; Alecia N. Septer (mBio, 2022)
ABSTRACT Interbacterial competition is prevalent in host-associated microbiota, where it can shape community structure and function, impacting host health in both positive and negative ways. However, the factors that permit bacteria to discriminate among their various neighbors for targeted elimination of competitors remain elusive. We identified a putative lipoprotein (TasL) in Vibrio species that mediates cell-cell attachment with a subset of target strains, allowing inhibitors to target specific competitors for elimination. Here, we describe this putative lipoprotein, which is associated with the broadly distributed type VI secretion system (T6SS), by studying symbiotic Vibrio fischeri, which uses the T6SS to compete for colonization sites in their squid host. We demonstrate that TasL allows V. fischeri cells to restrict T6SS-dependent killing to certain genotypes by selectively integrating competitor cells into aggregates while excluding other cell types. TasL is also required for T6SS-dependent competition within juvenile squid, indicating that the adhesion factor is active in the host. Because TasL homologs are found in other host-associated bacterial species, this newly described cell-cell attachment mechanism has the potential to impact microbiome structure within diverse hosts. IMPORTANCE T6SSs are broadly distributed interbacterial weapons that share an evolutionary history with bacteriophage. Because the T6SS can be used to kill neighboring cells, it can impact the spatial distribution and biological function of both free-living and host-associated microbial communities. Like their phage relatives, T6SS+ cells must sufficiently bind competitor cells to deliver their toxic effector proteins through the syringe-like apparatus. Although phage use receptor-binding proteins (RBPs) and tail fibers to selectively bind prey cells, the biophysical properties that mediate this cell-cell contact for T6SS-mediated killing remain unknown. Here, we identified a large, predicted lipoprotein that is coordinately expressed with T6SS proteins and facilitates the contact that is necessary for the T6SS-dependent elimination of competitors in a natural host. Similar to phage RBPs and tail fibers, this lipoprotein is required for T6SS+ cells to discriminate between prey and nonprey cell types, revealing new insight into prey selection during T6SS-mediated competition.